Mediation Effect of Perceived Fitness on the Relationship between Self-Efficacy and Sport Practice in Spanish Adolescents - Arribas-Galarraga, Silvia (Int J Environ Res Public Health, 2020)
There has been a decrease in sports practices among the adolescent population, and several authors have tried to identify variables that can explain this decrease by analyzing psychosocial aspects such as perceived fitness and self-efficacy. Therefore, the purpose of this research is to examine the association of perceived fitness and self-efficacy with sport practices and to determine whether perceived fitness is a mediator of the association between self-efficacy and sport practice in Spanish adolescents. The sample was composed of 882 students between 13 and 17 years old from Gipuzkoa (Spain). A descriptive, correlational and direct/indirect effect approach was used, using the PROCESS macro for Statistical Package for the Social Sciences (SPSS). Among the results obtained, it is highlighted on the one hand, that perceived fitness significantly correlates with both self-efficacy and sport practice, on the other hand, it is confirmed that perceived fitness is a mediator in the relationship between self-efficacy and sports practice. This finding highlights the importance of psychosocial aspects in efforts to increase sports practice.